2011
DOI: 10.1016/j.molcel.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Origin Activation in Response to Fork Stalling Leads to Chromosomal Instability at Fragile Sites

Abstract: Perturbed DNA replication in early stages of cancer development induces chromosomal instability preferentially at fragile sites. However, the molecular basis for this instability is unknown. Here, we show that even under normal growth conditions, replication fork progression along the fragile site, FRA16C, is slow and forks frequently stall at AT-rich sequences, leading to activation of additional origins to enable replication completion. Under mild replication stress, the frequency of stalling at AT-rich sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 57 publications
8
155
0
Order By: Relevance
“…We were able to sequence rare telomere-genomic fusions from LIG3 −/− :LIG4 −/− cells, reinforcing the notion of the coincidence of fusion foci with DNA replication, since LIG1 is the most rational protagonist mediating these LIG4-independent inter-chromosomal events (Arakawa et al 2012;Lu et al 2016). Further support arises from our finding of a conspicuous and significant association of LIG3 −/− :LIG4 −/− junctionproximal sequence with non-B DNA structures (Cooper et al 2011;Cer et al 2013) and a trend toward increased coincidence with fragile sites for LIG4 −/− junctions, implicating replication fork-stalling (Vissers et al 2009;Minca and Kowalski 2011;Ozeri-Galai et al 2011;Mizuno et al 2013) as a determinant of chromosome breakage and/or fusion. The A-NHEJ DNA polymerase theta also functions at the earliest stages of DNA replication and may, therefore, play a role in the introduction of the residual templated insertions resolved in these LIG4-deficient cells (Fernandez-Vidal et al 2014).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We were able to sequence rare telomere-genomic fusions from LIG3 −/− :LIG4 −/− cells, reinforcing the notion of the coincidence of fusion foci with DNA replication, since LIG1 is the most rational protagonist mediating these LIG4-independent inter-chromosomal events (Arakawa et al 2012;Lu et al 2016). Further support arises from our finding of a conspicuous and significant association of LIG3 −/− :LIG4 −/− junctionproximal sequence with non-B DNA structures (Cooper et al 2011;Cer et al 2013) and a trend toward increased coincidence with fragile sites for LIG4 −/− junctions, implicating replication fork-stalling (Vissers et al 2009;Minca and Kowalski 2011;Ozeri-Galai et al 2011;Mizuno et al 2013) as a determinant of chromosome breakage and/or fusion. The A-NHEJ DNA polymerase theta also functions at the earliest stages of DNA replication and may, therefore, play a role in the introduction of the residual templated insertions resolved in these LIG4-deficient cells (Fernandez-Vidal et al 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Repetitive DNA sequences (Cooper et al 2011), including fragile sites (Minca and Kowalski 2011;Thys et al 2015) and Alu (Gu et al 2015) have well-documented associations with genome instability via replication fork-stalling (Ozeri-Galai et al 2011) and stimulation of homology-based recombination processes (Mizuno et al 2013). Although we cannot determine the initiating DNA breakpoint for the telomere fusion events we have sequenced, we did not find any significant coincidence of inter-chromosomal (Cunningham et al 2015) and RefSeq (Pruitt et al 2014) curations-than expected by chance based on RefSeq human genome gene content estimate of 41.8%.…”
Section: A-and C-nhej Of Dysfunctional Human Telomeresmentioning
confidence: 99%
“…Accordingly, it has been reported that specific DNA sequences, such as [A/T]n and [AT/TA]n repeats, and/or the formation of non-B DNA secondary structures within aCFSs can inhibit replicative DNA polymerases (Shah et al, 2010) and the progression of replication forks (Zhang and Freudenreich, 2007). Recently, scarcity of replication origins, inefficient origin initiation, and failure to activate latent origins have all been proposed to play a role in delayed replication at specific aCFSs (Letessier et al, 2011;Ozeri-Galai et al, 2011). The Debatisse Laboratory reported the most important new findings in the recent years, showing that CFSs differ in different tissue types and are caused by the paucity of replication origins within the regions -i.e.…”
Section: General Featuresmentioning
confidence: 99%
“…11 Most importantly, direct evidence of fork stalling along an endogenous human fragile site has been recently gained using the FRA16C. 12 Replication dynamics studies demonstrate that in FRA3B, FRA7H and FRA16D replication initiates properly but then suffers difficulty in its progression, showing a delayed completion that is amplified by aphidicolin treatment. [13][14][15] Although the molecular basis leading from replication delay to breakage at CFS is still under intense investigation, it is thought that replication impairment is crucial for CFS outcome.…”
Section: Features Of Common Fragile Sites and Factorsmentioning
confidence: 99%
“…17 Interestingly, more recently, a third model has been developed that involves a combination of increased frequency of fork stalling throughout the fragile sites and the inability to activate additional origins following replication stress to rescue DNA replication. 12 Whatever the cause that leads to incomplete replication after fork slowing, unreplicated CFS regions are more susceptible to breakage.…”
Section: Features Of Common Fragile Sites and Factorsmentioning
confidence: 99%